2016
DOI: 10.1080/01140671.2016.1150308
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the genetic diversity in onion (Allium cepaL.) landraces from northwest Spain and comparison with the European variability

Abstract: Fifteen onion landraces from Galicia (northwest Spain) were characterised with a set of 25 microsatellite markers and the genetic variability harboured by this collection was compared with the surrounding diversity by comparison with a representative panel of European onion landraces. Twenty markers were polymorphic allowing the detection of 121 alleles. Ninety-one of these were identified in the Galician group (average of 4.6 distinct alleles per locus) and 9% of the total number of alleles were recorded as u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
2
21
1
Order By: Relevance
“…This correlation matrix overall summarized, that bulb size and phenol content has direct positive correlation with onion bulb yield. Similar findings reported by Singh et al, (2013), Raghuwanshi et al, (2016), Rivera et al, (2016) to identify the desirable parents so as to be utilized in onion breeding program for varietal development.…”
Section: Genetic Correlationsupporting
confidence: 82%
“…This correlation matrix overall summarized, that bulb size and phenol content has direct positive correlation with onion bulb yield. Similar findings reported by Singh et al, (2013), Raghuwanshi et al, (2016), Rivera et al, (2016) to identify the desirable parents so as to be utilized in onion breeding program for varietal development.…”
Section: Genetic Correlationsupporting
confidence: 82%
“…Despite the onion genotypes narrow genetic base, González have observed divergence between groups of genotypes using UPGMA algorithms. As well, Tocher method have been satisfactorily applied to expose the divergence between groups of genotypes (Akter et al, 2015;Khosa and Dhatt, 2015;Rivera et al, 2016). Crossing methods used in onion populations groups were separated at 70% dissimilarity; the threshold was established at the point of rupt change in the dendrogram branches, as recommended by Cruz et al (2012).…”
Section: Resultsmentioning
confidence: 99%
“…the onion genotypes narrow genetic base, González-Pérez et al (2015) also have observed divergence between groups of genotypes using UPGMA algorithms. As well, Tocher method have been satisfactorily applied to expose the divergence between groups of genotypes (Akter et al, 2015;Khosa and Dhatt, 2015;Rivera et al, 2016).…”
Section: ©Funpecmentioning
confidence: 99%
See 1 more Smart Citation
“…The modern varieties were derived from heirloom varieties maintained within traditional farming systems. These varieties form open-pollinated, heterozygote, and heterogeneous populations [7]. Korea, Japan, USA, and many countries around the globe developed open-pollinated, short duration, and early spring type to summer type onion varieties.…”
Section: Introductionmentioning
confidence: 99%